2016
DOI: 10.1111/soin.12127
|View full text |Cite
|
Sign up to set email alerts
|

Transnormativity: A New Concept and Its Validation through Documentary Film About Transgender Men

Abstract: While prior research has called attention to how medically based, normative understandings of sex and gender place undue restrictions on transgender people's autonomy, there has yet to be an attempt to consolidate this research into a recognizable concept that is situated within existing theoretical frameworks. This article uses documentary films focused on transgender men as an empirical example to develop the concept of transnormativity. Transnormativity describes the specific framework to which transgender … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
137
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(158 citation statements)
references
References 39 publications
3
137
0
9
Order By: Relevance
“…On top of their management of an already marginalized identity, trans people felt they had to present a specific version of transness—what Johnson () calls Transnormativity—to get what they needed to proceed with their transition.…”
Section: Resultsmentioning
confidence: 99%
“…On top of their management of an already marginalized identity, trans people felt they had to present a specific version of transness—what Johnson () calls Transnormativity—to get what they needed to proceed with their transition.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the primary model for understanding trans‐ness in the United States asserts that transgender people were “born in the wrong body” and transition to the “opposite” gender (Bettcher, ; Serano, ). While this does not describe all people's experiences, and not everyone aims to pass as cisgender, the belief that they should or do feel this way constitutes an ideology that Johnson () calls transnormativity. Individual trans people, gatekeeping institutions, and social discourses all promote and enforce transnormative expectations (Johnson, ).…”
Section: Transgender Communities: Too Trans or Not Trans Enough?mentioning
confidence: 99%
“…While this does not describe all people's experiences, and not everyone aims to pass as cisgender, the belief that they should or do feel this way constitutes an ideology that Johnson () calls transnormativity. Individual trans people, gatekeeping institutions, and social discourses all promote and enforce transnormative expectations (Johnson, ). But while transnormativity is only one of many gender ideologies used to police trans people's gender identities and expression (shuster, ), it plays a particularly salient role in the process of gatekeeping around the trans community.…”
Section: Transgender Communities: Too Trans or Not Trans Enough?mentioning
confidence: 99%
“…Many scholars have shown that the medical model restricts trans people in legal, social and medical settings while simultaneously providing avenues to gender-affirming care (Burke 2011, Butler 2006, Koenig 2011, Meadow 2010, Romeo 2004, Spade 2003. The double-edged effects of trans diagnosis arise most noticeably in the form of gatekeeping, or the use of the medical model and associated diagnostic standards as a normative accountability structure (Johnson 2015(Johnson , 2016) that empowers trans people who fit its criteria and constrains those who do not. Specifically, scholars have documented the ways that the medical model operates as a kind of litmus test for determining who may access (i) gender affirming medical care (Drescher et al 2012, Spade 2003, (ii) social support and/or validation from both transgender and cisgender (i.e.…”
Section: Medicalisation Of Trans Experiencementioning
confidence: 99%